Integrating video-game music into Electone pedagogy in China: investigating learning process and outcomes - Wei, Jiachen; Songsiengchai, Saifon; Liu, Yaoping; Laknapichonchat, Tassanee (Frontiers in Education, 2025)
Available studies have examined game’s impact on music education from the learning outcome perspective. This sequential mixed-method design attempted to explore the impact of video-game music as Electone pedagogy on students’ learning process and outcome. The study aimed to explore learners’ motivation, engagement, skills, and creativity and teachers’ challenges in applying this approach. The participants involved 50 students and 2 Electone teachers. The quantitative and qualitative data were collected using t-tests and interviews. The quantitative results exhibited that incorporating the video game Honor of King could boost students’ levels of motivation, engagement, Electone skills, and creativity. The challenges to utilising this game were the necessity of aligning game mechanics with Electone theory. Students may occasionally prioritise gameplay over instrumental accuracy, which could potentially detract from the achievement of Electone learning objectives. This study also offers pedagogical implications on how to apply games as a pedagogical tool in the Electone course.